2022
DOI: 10.1016/j.jmh.2022.100083
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in international immigrants: Profile and vulnerability of cases residing in the municipality of São Paulo, Brazil

Abstract: Objective To analyze the profile of immigrants with tuberculosis (TB) and to identify the associated vulnerability characteristics. Methods A cross-sectional study which used TB-WEB data from cases residing in São Paulo in 2016 (203 immigrants and 6,069 non-immigrants). The variables were analyzed using prevalence ratio and confidence intervals. Results Among the immigrant cases, 67% were Bolivians. When compared to non-immigrants, immigrants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(32 reference statements)
1
0
0
Order By: Relevance
“…The outcomes measured in this study showed a lower percentage of cure than recommended by the World Health Organization - WHO - (at least 85% of patients cured) [ 22 ] and a percentage of dropout higher than the goal established by the WHO (at most 5% of treatment dropouts) [ 22 ] in both migrants and non-migrants. A previous study conducted in the northern region of Brazil showed similar results for the general population [ 29 ] as well as one conducted in the Southeast region in migrants and non-migrants with TB [ 30 ]. All these results seem to point to operational failures in the provision of intervention and services aimed at the clinical management of TB in different contexts of the country.…”
Section: Discussionsupporting
confidence: 71%
“…The outcomes measured in this study showed a lower percentage of cure than recommended by the World Health Organization - WHO - (at least 85% of patients cured) [ 22 ] and a percentage of dropout higher than the goal established by the WHO (at most 5% of treatment dropouts) [ 22 ] in both migrants and non-migrants. A previous study conducted in the northern region of Brazil showed similar results for the general population [ 29 ] as well as one conducted in the Southeast region in migrants and non-migrants with TB [ 30 ]. All these results seem to point to operational failures in the provision of intervention and services aimed at the clinical management of TB in different contexts of the country.…”
Section: Discussionsupporting
confidence: 71%